DYNAMICS OF PREFERENTIAL MAINTENANCE OF CITIZENS WITH ANTIHYPERTENSIVE DRUGS AT THE EXPENSE OF THE REGIONAL BUDGET - I. I. Lavrentyeva; A. I. Khokhlov; I. N. Kagramanyan; T. A. Gorokhova (Фармакоэкономика, 2015)
In Yaroslavl region the death rate and physical inability indicators caused by cardiovascular diseases (including an arterial hypertension) take a leading place and exceed average indicators in Russia. For effective preventive maintenance and treatment of the given pathology maintenance of all categories needing necessary medical products is very significant. In the conditions of refusal of the most part of the population of the free medicinal help according to Federal Law №178-ФЗ from 7/17/1999 the increasing loading on medicinal maintenance lays down on the regional budget. The analysis of dynamics of maintenance sick of an arterial hypertension at the expense of the regional budget for 2008-2011 has revealed expansion of structure of assortment according to the modern recommendations, essential increase in quantity and cost released antihypertensive drugs that are caused by decrease in average costof one prescription.